Synthesis of a Novel Filtrate Reducer and Its Application in Water-Based Drilling Fluid for Ultra-High-Temperature Reservoirs. (29th October 2021) - Qiao, Dongyu; Ye, Zhongbin; Tang, Lei; Zheng, Yiping; Wang, Xindong; Lai, Nanjun
Abstract : The high-temperature stability and filtration property controlling of ultra-high-temperature water-based drilling fluids is a worldwide problem. To resolve this problem, a high-temperature-resistant quaternary copolymer (HTRTP) was synthesized based on molecular structure optimization design and monomer optimization. The physical and chemical properties were characterized by infrared spectroscopy, thermal weight, and spectrophotometry, and their temperature and salt resistance was evaluated in different drilling fluids, combined with adsorption, particle size analysis, and stability test. The results show that the thermal stability of HTRTP is very strong, and the initial temperature of thermal decomposition is above 320°C. The salt resistance of HTRTP is more than 162 g/L, and the calcium resistance is more than 5000 mg/L, which is equivalent to the foreign temperature-resistant polymer DCL-a, and is superior to the domestic metal ion viscosity increasing fluid loss agent PMHA-II for drilling fluids. It has excellent high-temperature resistance (245°C) and fluid loss reduction effect in fresh water base mud, fresh water weighted base mud, saturated brine base mud, and composite salt water base mud, which is better than foreign DCL-a (245°C) and domestic PMHA (220°C). The adsorption capacity of HTRTP on clay particles is large and firm, and the adsorption capacity changes little under the change of chemical environment and temperature. Both before and after HTRTP aging (245°C/16 h), the permeability of filter cake can be significantly reduced and its compressibility can be improved. By optimizing the particle size gradation of the drilling fluid and enhancing the colloid stability of the system, HTRTP can improve the filtration building capacity of the drilling fluid and reduce the filtration volume. The development of antithermal polymer provides a key treatment agent for the study of anti-high-temperature-resistant saline-based drilling fluid.